A Review on Prevalence and Risk Factors of Musculoskeletal Disorders (Msds) Among VDT Users - Shafika Mohamad, Siti; Nasrull Abdol Rahman, Mohd; ., . (International Journal of Engineering and Technology, 2018)
This review aims to to identify the prevalence of computer work related to musculoskeletal disorders among Video Display Terminal users.The association between risk factors and musculoskeletal disorders was also identified. Data from 1990 until 2015 was retrieved using electronic databases. The review was done based on computer work, office risk factors, musculoskeletal disorders, working posture, office components and office environment. Epidemiology studies show that physical exposure has a moderate and to strong association with Computer Work-Related Musculoskeletal Disorders. Sixteen risk factors for office workstation swith significant associations with body part exposure outcomeswere identified. Through the studies, it was found that computer-related risk factors correspond with Musculoskeletal Disorders (MSDs) including awkward postures, long duration of computer use, work involving repetitive processes and the office environmentÂ Â
Keywords: ergonomic risk factors; computer work; musculoskeletal disorders; office workstation